UJI AKTIVITAS ENZIM FITASE YANG DIHASILKAN OLEH Aspergillus niger DAN Neurospora sp. PADA KONDISI FERMENTASI YANG BERBEDA - Devi Ayu Ningsih; Endang Kusdiyantini; Budi Raharjo (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
Phytase (E.C 3.1.3.8) is an important enzyme to overcome high phytic acid in livestock feed since this enzyme has the ability to hydrolyze phytic acid contained in feed material into inositol, glucose and organic phosphorus compound. This phytase enzyme can be produced by Aspergillus niger and Neurospora sp. The purpose of this study is to obtain the condition of fermentation by Aspergillus niger dan Neurospora sp. which is optimal in the production of phytase enzyme.The treatment of fermentation condition includes different pH, temperature and addition of C source (glucose). The production of enzyme was carried out in media containing glucose KCl, MgSO4.7H20, K2HPO4, NaOH with the addition of Palm Oil Mill Effluent. Mold was grown in liquid medium and measured the activity of phytase enzyme using spectophotometry. This study used a Complete Randomized Design factorial pattern with two factors. The first assaying ANOVA used a variation in the concentration of Palm Oil Mill Effluent with pH while, the second assaying used a variation in the concentration of Palm Oil Mill Effluent with temperature, and third assaying used a variation of glucose concentration with incubation times. Each factor was repeated 3 times. The data obtained were then analyzed using Analysis of Variance (ANOVA). The result of observation showed optimal phytase enzyme activity for A. Niger at pH 5 onthe temperature of 350C as much as 0.241 and 0.258 U U/ml while Neurospora sp. at pH 6 on the temperature of 350C as much as 0,273 and 0,253 U/ml. The addition of glucose experienced optimal phytase activity for Aspergillus niger as much as 0,099 U/ml at incubation time in 96 hours and Neurospora sp. as much as 0,152 U/ml in 48 hours will then decrease at subsequent incubation time. Keywords: phytase, Palm Oil Mill Effluent, pH, A. niger and Neurospora sp.